Utilizing Concept Maps to Enhance Students’ Writing Skills - Susi Astiantih; Sofyan Sukwara Akfan (Journal of Languages and Language Teaching, 2023)
Writing is one of the difficult skills in a language. The difficulty of writing includes spelling, punctuation, word choices, and so on. However, many students already studied writing since middle school. As a result, many of them have not yet been able to write correctly. The aim of this paper is to find out an increase in descriptive writing skills by utilizing a concept map. This study used descriptive and quantitative research on car design. The sample was 20 students using purposive sampling. The instrument was an objective test. The procedure for collecting data used to test distribution and analysis data. The finding showed that students had excellent to very good achievement in writing skills through concept maps. It was indicated by the results of the mean score in the post-test.  it indicates that the student’s writing ability was in good to Very Good criteria. It means that writing a descriptive text with a concept map was better than writing descriptive text without a concept map. This research found the pedagogical implication that concept maps help teachers in providing active learning, creative, effective, and fun for students according to learning style. Newly, it can increase awareness of teachers on students’ learning difficulties and efforts to overcome their obstacles in writing.